Tunable ferroelectricity in Ruddlesden-Popper halide perovskites - Zhang, Qiannan (2020)
Ruddlesden-Popper (RP) halide perovskites are the new kids on the block for high-performance perovskite photovoltaics with excellent ambient stability. The layered nature of these perovskites offers an exciting possibility of harnessing their ferroelectric property for photovoltaics. Adjacent polar domains in a ferroelectric material allow the spatial separation of electrons and holes. Presently, the structure-function properties governing the ferroelectric behavior of RP perovskites are an open question. Herein, we realize tunable ferroelectricity in 2-phenylethylammonium (PEA) and methylammonium (MA) RP perovskite (PEA)2(MA) n̅-1Pb n̅I3 n̅+1. Second harmonic generation (SHG) confirms the noncentrosymmetric nature of these polycrystalline thin films, whereas piezoresponse force microscopy and polarization-electric field measurements validate the microscopic and macroscopic ferroelectric properties. Temperature-dependent SHG and dielectric constant measurements uncover a phase transition temperature at around 170 °C in these films. Extensive molecular dynamics simulations support the experimental results and identified the correlated reorientation of MA molecules and ion translations as the source of ferroelectricity. Current-voltage characteristics in the dark reveal the persistence of hysteresis in these devices, which has profound implications for light-harvesting and light-emitting applications. Importantly, our findings disclose a viable approach for engineering the ferroelectric properties of RP perovskites that may unlock new functionalities for perovskite optoelectronics.